Pengembangan Dashboard Data untuk Optimalisasi Layanan dan Literasi Perpustakaan di SD Negeri 2 Berkoh - Trihastuti Yuniati; Amalia Beladinna Arifa; Shintia Dwi Alika; Atika Ratna Dewi; Habibah Ratna Fadhila Islami Hana; Vania Noverina; Aprianti Ika Larasati (BADAN PENERBIT STIEPARI PRESS, 2025)
The development of library management constitutes a crucial aspect in enhancing the quality of education and fostering community literacy. School libraries fulfill a fundamental role as vital learning resource centers; however, numerous institutions continue to encounter significant challenges in operational data management and the effective utilization of technology. This community service initiative aimed to develop and implement a